A frameshift variant in the SIRPB1 gene confers susceptibility to Crohn’s disease in a Chinese population - Tang, Jian; Wan, Xingyang; Zhang, JunXiao; Diao, Na; Zhang, Caibin; Gao, Xiang; Ren, Donglin (Frontiers in Genetics, 2023)
Background: Crohn’s disease (CD), a chronic gastrointestinal inflammatory disease, is increasing in China. With a focus on Han Chinese families with CD, the aim of this study was to find genetic variations that increase CD susceptibility by genome sequencing, genetic association, expression, and functional research. Materials and methods: We performed family-based genome sequencing (WGS) analysis on 24 patients with CD from 12 families and then filtered shared potential causal variants by incorporating association results from meta-analyses of CD GWAS and immunology genes and in silico variant effect prediction algorithms. Replication analyses were performed in an independent cohort including 381 patients with CD and 381 control subjects. Results: There were 92 genetic variants significantly associated with CD in Chinese individuals. Among them, 61 candidate loci were validated in replication analyses. As a result, patients carrying a rare frameshift variant (c.1143_1144insG; p. Leu381_Leu382fs) in gene SIRPB1 had significantly higher risk to develop CD (P = 0.03, OR 4.59, 95% CI 0.98-21.36, 81.82% vs 49.53%). The frameshift variation induced tyrosine phosphorylation of Syk, Akt, and Jak2, elevated the expression of SIRPB1 at the mRNA and protein levels, activated DAP12, and controlled the activation of NF-κB in macrophages. Additionally, it promoted the synthesis of the pro-inflammatory cytokines IL-1, TNF-, and IL-6. Conclusion: Our results suggest that the rare gain-of-function frameshift variant in SIRPB1 is associated in Han Chinese patients with CD. The functional mechanism of SIRPB1 and its downstream inflammatory pathways was preliminarily explored in CD.